1996
DOI: 10.1016/0014-5793(96)00227-x
|View full text |Cite
|
Sign up to set email alerts
|

H2O2 renders cells accessible to lysis by exogenous phospholipase A2: a novel mechanism for cell damage in inflammatory processes

Abstract: Phospholipase A2 (PLA2) and H202, secreted from activated inflammatory cells, play a central role in the tissue damage occurring in inflammatory processes. However, while exogenous PLA2 alone does not cause cell lysis, it readily does so when acting with H202. We have found that H202 degrades cell surface proteoglycans, thus rendering the membrane PL accessible to hydrolysis by exogenous PLA2. This novel mechanism introduces a role for cell surface proteoglycans in protection of cells from damage by pro-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 26 publications
(28 reference statements)
0
41
0
Order By: Relevance
“…29 35 In a study of the synergistic action of hydrogen peroxide and sPLA 2 we have previously observed that only after the cell surface GAGs are degraded by hydrogen peroxide is the cell membrane rendered accessible to lysis by exogenous sPLA 2 . 32 Although the relationship between GAG function and the action of inflammatory mediators is not unequivocally clear, it is well documented that GAG stripping exposes cells and tissues to damaging agents. Accordingly, it has been proposed that enrichment of cell surface GAGs would assist in protecting the cell from infection and inflammatory/allergic assaults.…”
Section: Discussionmentioning
confidence: 99%
“…29 35 In a study of the synergistic action of hydrogen peroxide and sPLA 2 we have previously observed that only after the cell surface GAGs are degraded by hydrogen peroxide is the cell membrane rendered accessible to lysis by exogenous sPLA 2 . 32 Although the relationship between GAG function and the action of inflammatory mediators is not unequivocally clear, it is well documented that GAG stripping exposes cells and tissues to damaging agents. Accordingly, it has been proposed that enrichment of cell surface GAGs would assist in protecting the cell from infection and inflammatory/allergic assaults.…”
Section: Discussionmentioning
confidence: 99%
“…Then reactive oxygen entered into the cells and broke the balance between antioxidant defenses (antioxidant enzymes) and free radicals generation, which caused molecular damage and cell injury. In addition, H 2 O 2 reacted with metal ions in cells to generate extremely highly toxic hydroxyl radicals through the Fenton reaction (Dan et al, 1996). The additional CE or fraction concentration in the medium was 1 mg/mL.…”
Section: Antioxidant Activity Of Molecular-weight Fractions Throughmentioning
confidence: 99%
“…The mechanisms by which combinations of oxidants, membrane-perforators and proteinases injure cells might involve a removal, by oxidants and perhaps also by proteinases, of membrane-associated glycosaminoglycans which facilitated the exposure the 'naked' plasma membrane to an attack by the membrane-perforating agents (Dan et al, 1996).…”
Section: The Synergism Concept Of Cellular Injurymentioning
confidence: 99%